2008
DOI: 10.1556/aagr.56.2008.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the drought and heat stress response of green bean ( Phaseolus vulgaris L.) varieties under phytotronic conditions

Abstract: The drought tolerance of six green-and yellow-podded varieties of green beans with different genetic backgrounds was tested in the phytotron. During the week prior to flowering the plants were kept either at 25/15°C (day/night) or at high temperature (30/15°C), with RH 75% and optimum water supplies. The heat-stressed plants were then divided into three groups; the first was returned to the control (25/15°C) chamber (RH 75%, optimum water supplies), while the second and third were exposed to mild drought stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The south part of Anatolia is predicted to be one of the most heat-affected regions by climate change. Yield reduction due to the heat stress effects was also similar to that which was explained by Nemeskéri, Remenyik [64], who showed that a decrease in yield is the result of the alteration of the reproductive organs, which are particularly affected by heat stress [20,26,[65][66][67]. The role of genes in the tolerance of bean species to heat stress is complex and can vary depending on the specific species and trait being examined.…”
Section: Discussionsupporting
confidence: 78%
“…The south part of Anatolia is predicted to be one of the most heat-affected regions by climate change. Yield reduction due to the heat stress effects was also similar to that which was explained by Nemeskéri, Remenyik [64], who showed that a decrease in yield is the result of the alteration of the reproductive organs, which are particularly affected by heat stress [20,26,[65][66][67]. The role of genes in the tolerance of bean species to heat stress is complex and can vary depending on the specific species and trait being examined.…”
Section: Discussionsupporting
confidence: 78%
“…In the leaves of Idared, the ACW content was high, which is the sign of drought according to our earlier findings Ecological drought resistance and adaptability of apple varieties 119 (Nemeskéri et al 2008). In Jonagold, the leaves contain initially few ACL antioxidants, which increases during the drought (July 8 -23) and signalises the defence against high temperature and radiation (Table 5).…”
Section: Changes Of Antioxydant Content Of the Leavessupporting
confidence: 65%
“…There are several methods serving the measurement of the water content of plants, but their efficacy depends on the purpose of the examination (Jones, 2007). In some vegetables, one week of drought may cause visible symptoms, leaves turn yellow and flowers abscise (Nemeskéri et al, 2008). In fruit trees, only utterly heavy drought of soil and of atmosphere may cause conspicuous symptoms, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Both the phytotron and field experiments illustrated that the yellow-podded green bean varieties respond to drought more sensitively than green-podded ones (Nemeskéri et al, 2008(Nemeskéri et al, , 2010. This was confirmed by the decrease in chlorophyll a and b components and the antioxidant capacity of water soluble (ACW) substances in the leaves of yellowpodded beans compared to the well-watered plants during flowering at severe drought stress in the phytotron, while there was not remarkable change in comparison with greenpodded ones (Table 2).…”
Section: Defence Strategies In Beansmentioning
confidence: 77%